Diversifying and de-growing the circular economy: Radical social transformation in a resource-scarce world. (September 2016) - Hobson, Kersty; Lynch, Nicholas
Highlights: The Circular Economy (CE) has gained momentum in the EU as an agenda for economic growth and a sustainable future. The CE agenda depoliticizes the role of the consumer and over-prioritizes technologically mediated forms of engagement. The Sharing Economy is discussed to illuminate how consumption practices develop inconsistencies between expected benefits and socio-environmental impacts. 'Degrowth' and 'the diverse economy' are presented as alternative socio-economic visions for a more radical CE. Abstract: Programmes and policies for a Circular Economy (CE) are fast becoming key to regional and international plans for creating sustainable futures. Framed as a technologically driven and economically profitable vision of continued growth in a resource-scarce world, the CE has of late been taken up by the European Commission and global business leaders alike. However, within CE debates and documentation, little is said about the social and political implications of such transformative agendas. Whilst CE proponents claim their agenda is 'radical', this paper outlines its inability to address many deeply embedded challenges around issues of consumption and the consumer, echoing as it does the problematic (and arguably failed) agendas of sustainable consumption/lifestyles. Using the Sharing Economy as an example, we argue here that the ontological and sociological assumptions of the CE must be open to more 'radical' critique and reconsideration if this agenda is to deliver the profound transformations that its advocates claim are within our collective reach.